Combining InSAR and GPS to Determine Transient Movement and Thickness of a Seasonally Active Low‐Gradient Translational Landslide - Xie Hu; Zhong Lu; Thomas C. Pierson; Rebecca Kramer; David L. George (Geophysical Research Letters)
Abstract The combined application of continuous Global Positioning System data (high temporal resolution) with spaceborne interferometric synthetic aperture radar data (high spatial resolution) can reveal much more about the complexity of large landslide movement than is possible with geodetic measurements tied to only a few specific measurement sites. This approach is applied to an ~4 km2 reactivated translational landslide in the Columbia River Gorge (Washington State), which moves mainly during the winter rainy season. Results reveal the complex three‐dimensional shape of the landslide mass, how onset of sliding relates to cumulative rainfall, how surface velocity during sliding varies with location on the topographically complex landslide surface, and how the ground surface subsides slightly in weeks prior to downslope sliding.